PW 1641 Establishing an injury research centre in nepal; challenges and opportunities. (November 2018) - Mytton, Julie; Pant, Puspa; Ellis, Matthew; Baset, Kamran ul; Joshi, Sunil Kumar
Abstract : In November 2016 the UK National Institute for Health Research launched a Global Health Research Programme to promote collaboration between UK Universities and countries eligible for receipt of UK Government Overseas Development Aid. The University of the West of England, Bristol, in collaboration with Kathmandu Medical College Nepal, and other organisations including MIRA (Mother and Infant Research Activities) secured three years funding to establish a Nepal Injury Research Centre, commencing July 2017. The aim of the Centre is to build a sustainable research network and infrastructure with the capacity and capability for injury research. We will use a public health approach to provide the evidence for behavioural, environmental and legislative change for the prevention of all types of injury and first response, piloting activities in Makwanpur district of Nepal. The opportunities afforded by this award are significant; to recruit and develop a research workforce capable of future independence, to build a relationship with strategic decision makers that will align the research with national priorities and provide a forum through which evidence can influence policy and legislation. The challenges are significant too; to identify and address evidence gaps within the limited duration of the award, to balance national priorities with other injury issues not currently recognised, to establish a mechanism to monitor injuries that can be used to measure change, and all within a context of marked social and political development. The presentation will describe the strategies we are using to meet the challenges, including working with, and learning from, established units such as the Centre for Injury Prevention Research Bangladesh, and advocating for a National Injury Advisory Committee in Nepal. This model of funding and the strategies taken in Nepal have the potential to influence the development of injury research capability and capacity in other low and middle income countries.